Utilisation and Promotion of Institutional Repositories at the Institute of Finance Management to Enhance Research and Institutional Visibility in Tanzania - Kyumana, Valeria; Msonge, Vincent T (Zambia Journal of Library & Information Science (ZAJLIS ), ISSN: 2708-2695; Vol 9 No 1 (2025): Zambia Journal of Library & Information ScienceDO - 10.53974/unza.zajlis.9.1.170, 2025)
This study examined factors hindering the effective utilization of Institutional Repositories (IRs) at the Institute of Finance Management (IFM) in Tanzania, comparing insights from four higher learning institutions. Its specific objectives were to identify challenges affecting IR utilization at IFM, analyze strategies adopted by peer universities, and propose actionable measures for IFM to enhance IR engagement and institutional visibility. Using a qualitative approach, data were collected from 14 librarians (6 from IFM and 8 from other universities) and 2 ICT officials, all purposively selected. Findings revealed that IFM’s low IR utilization stems from the absence of a clear IR policy and limited awareness of IR benefits among academic staff and management. In contrast, peer institutions emphasized proactive marketing, policy frameworks, and compliance mechanisms to boost participation. The study concludes that strategic interventions—including policy formulation, awareness campaigns, and mandatory submission guidelines—are critical to improving IR utilisation. By addressing these gaps, IFM can leverage IRs to increase research visibility and academic impact, aligning with successful practices in similar Tanzanian universities.